Concussive biomechanics in a women`s soccer player: a validation clinical case report - Sayre, H. D.; Bowman, T. G. (International Journal of Athletic Therapy & Training, 2023)
A concussed 19-year-old female midfielder on an National Collegiate Athletic Association (NCAA) Division III soccer team reported to the athletic training clinic complaining of a headache that began 4 days previously during a game where she headed several long punts. Despite delayed reporting, the patient returned to full participation without complication 13 days after her injury. The biomechanical data for the impacts she received on the day of injury were much lower than those presented in the literature as causing concussion for male athletes. Therefore, impact magnitude should not be used as an indicator for injury, as smaller, seemingly insignificant impacts can cause concussion.